2017
DOI: 10.1016/j.cobeha.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological basis of individual variation in stimulus-reward learning

Abstract: Cues in the environment can guide behavior in adaptive ways, leading one towards valuable resources such as food, water, or a potential mate. However, cues in the environment may also serve as powerful motivators that lead to maladaptive patterns of behavior, such as addiction. Importantly, and central to this article, there is considerable individual variation in the extent to which reward cues gain motivational control over behavior. Here we describe an animal model that captures this individual variation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 60 publications
5
102
0
1
Order By: Relevance
“…The sign-tracker/goal-tracker animal model has allowed us to parse the incentive from the predictive value of reward cues and to begin to identify the neural networks underlying these distinct forms of learning (Flagel et al 2011a, Yager et al 2015, Flagel and Robinson 2017, Haight et al 2017). Most studies to-date that have exploited this model of individual variation to study the underlying brain mechanisms have focused on neuronal responses to food-cues that were attributed with incentive or predictive value following classical Pavlovian conditioning paradigms (Flagel et al 2010, Flagel et al 2011b, Haight and Flagel 2014, Haight et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sign-tracker/goal-tracker animal model has allowed us to parse the incentive from the predictive value of reward cues and to begin to identify the neural networks underlying these distinct forms of learning (Flagel et al 2011a, Yager et al 2015, Flagel and Robinson 2017, Haight et al 2017). Most studies to-date that have exploited this model of individual variation to study the underlying brain mechanisms have focused on neuronal responses to food-cues that were attributed with incentive or predictive value following classical Pavlovian conditioning paradigms (Flagel et al 2010, Flagel et al 2011b, Haight and Flagel 2014, Haight et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The sign-tracker/goal-tracker animal model has provided a novel foundation to dissociate the neural mechanisms underlying predictive vs. incentive learning (Flagel et al 2017). Indeed, using this model, it has been shown that food- and drug-associated cues engage different circuitry in STs vs. GTs (Flagel et al 2011a, Yager et al 2015, Haight et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They argue that dopamine acts selectively, attributing incentive salience to cues for reward in some subjects, for whom reward cues come to powerfully motivate and control behavior. Flagel and Robinson (2017) argue that the difference between sign-and goal-tracking may relate to a difference in dopamine signaling in the core of the nucleus accumbens, an area critical for the attribution of incentive salience to cues for reward. Differences in dopamine transporter expression, associated with faster dopamine uptake in the core of the accumbens, are seen in animals that sign-track (Flagel & Robinson 2017;Signer, Guptaroy & Austin et al, 2016;Flagel et al, 2010;Flagel, Watson, Robinson & Akil, 2007).…”
Section: Why Do Individuals Differ?mentioning
confidence: 99%
“…This review describes research on selected populations of rats which, at the extreme ends of the construct, exhibit a bias for bottom-up or cue-driven attention (sign-trackers, STs), or relatively high levels of top-down, goal-driven attentional control (goal-trackers, GTs). Below we will review the available evidence on the role of major neuromodulator systems in mediating these opponent cognitive styles (for reviews focusing primarily on the relevance of these rats in addiction research see Flagel, Akil, & Robinson, 2009; Flagel & Robinson, 2017; Robinson, Yager, Cogan, & Saunders, 2014). …”
mentioning
confidence: 99%